ANALISIS ANGGARAN BIAYA PEMASARAN SEBAGAI ALAT PENILAIAN KINERJA PADA PT. PENERBIT ERLANGGA CABANG BENGKULU - Wirosman Wehalo; Nani Halima Zahara (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
Wirosman Wehalo, Nani Halima Zahara; The purpose of this study was to analyze whether the marketing budget can be used as a performance assessment tool company, the company is focused on trading company where any Copyrighted has been protected by the Act during the period of 2007 until today. Types of research used in this study was a comparative descriptive study was to compare the similarities and differences in two or more of the facts and the object properties in the framework based on certain carefully. Research object in this study is PT. The publisher Erlangga Bengkulu branch. from 2007 to 2012 showed the budget is already functioning as a performance assessment tool, because in assessing the performance of each branch of the company to compare between the budget and the realization that the cause was traced. Key words: Marketing costs, revenues, performance